SOSIO-ECONOMIC DYNAMICS OF STREET BOOK VENDORS IN THE KWITANG BOOK MARKET 2002 – 2008: Dinamika Sosial Ekonomi Pedagang Buku Kaki Lima Di Pasar Buku Kwitang 2002 - 2008 - Vriska Nanda Putri Siregar; Uf Saraswati (SOSIOEDUKASI, 2026)
This study discusses the socio-economic conditions of street vendors in the Kwitang Book Market in the period from 2002 to 2008. The purpose of this research is to find out in depth the development of the used book trade, socio-economic dynamics, and identification related to the regulation that occurs in the Kwitang Book Market.The type of method used in this study is the historical method. Data collection was carried out through observation, interviews, archival tracing and media reports compared with literature reviews.This study shows that the Kwitang Book Market has experienced an increase in economic activity influenced by location, transportation, and developing popular culture. The social dynamics that occur between street vendors at the Kwitang Book Market are characterized by the close relationship between traders who form social capital to support the sustainability of their businesses. The dynamics that occurred must stop when the government implemented a control policy to restore sidewalks as green open spaces. This of course has a significant impact on traders who have to give up their livelihoods.